Pengaruh Perilaku Belajar Peserta Didik Terhadap Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar - Akbar, Azizullah Putri; Komarudin, Yooke Tjuparmah (Universitas Pendidikan Indonesia, 2015)
Abstract. This research is motivated by the emergence of the information technology era in which library turns as the place for acquiring information, notably in school. Based on that background, this research is focused on the student's attitude and behavior, and student's learning interest towards school library utilization as a learning resource. The student's behavior was observed across the x-axis and the utilization of library as a learning resource in y-axis. Student's attitude was measured by means of attitude sub-variable which consists of three indicators: cognitive, affective, and conative. Student's behavior was measured by two indicators, namely learning behavior and reading behavior. Furthermore, student's learning interest consists of behave, attention and feeling. This research employs a descriptive design with some quantification to enhance the analysis. Furthermore, the data are collected by using closed questionnaire and Likert Scale. Then the data are analyzed by using correlation analysis and simple linear regression. The results revealed that student's learning behavior has a significant connection and influence (0.841) towards the utilization of school library as a learning resource. Based on this result, it can be recommended that school libraries are expected to develop its materials to increase the level of student's attitude, behavior and interest regarding to utilize library as a learning resource.Keywords: learning attitude, library materials utilization, learning resources, students.Abstrak. Masalah yang menjadi kajian dalam penelitian ini difokuskan pada sikap, kebiasaan, dan minat belajar peserta didik terhadap pemanfaatan perpustakaan sekolah sebagai sumber belajar. Penelitian ini terdiri dari perilaku belajar peserta didik (X) dan pemanfaatan perpustakaan sekolah sebagai sumber belajar (Y). Perilaku belajar peserta didik diukur melalui sub variabel sikap yang terdiri dari tiga indikator yaitu kognitif, afektif, dan konatif, dan kebiasaan terdiri dari dua indikator yaitu kebiasaan belajar dan kebiasaan membaca, sedangkan minat belajar terdiri dari perbuatan, perhatian, dan perasaan. Metode penelitian yang digunakan adalah studi deskriptif dengan pendekatan kuantitatif. Teknik pengumpulan dataÂ menggunakan kuesioner tertutup dengan menggunakan Skala Likert dan menggunakan analisis data korelasi, serta untuk melihat besar pengaruhnya menggunakan koefisien determinasi dan regresi linier sederhana. Berdasarkan hasil analisis data, diketahui bahwa perilaku belajar peserta didik mempunyai tingkat hubungan dan berpengaruh signifikan terhadap pemanfaatan perpustakaansekolah sebagai sumber belajar, dengan signifikansi pengaruh sebesar 0,841. Rekomendasi pada penelitian ini perpustakaan sekolah diharapkan dapat mengembangkan bahan perpustakaan sehingga meningkatkan keberagaman sikap, kebiasaan, dan minat belajar peserta didik untuk memanfaatkan perpustakaan sekolah sebagai sumber belajar.Kata kunci : Perilaku belajar, Pemanfatan bahan perpustakaan, Sumber belajardan Peserta didik